Portuguese fisheries in seamounts of Madeira-Tore (NE Atlantic). (January 2019) - Campos, A.; Lopes, P.; Fonseca, P.; Figueiredo, I.; Henriques, V.; Gouveia, N.; Delgado, J.; Gouveia, L.; Amorim, A.; Araujo, G.; Drago, T.; dos Santos, A.
Abstract: The activity of the Portuguese fishing fleet operating near seamounts of the Madeira Tore geologic complex was analyzed. The main objective is to identify the different fisheries taking place in the area, characterize the spatial patterns of vessels activity and estimate the fishing intensity, thus contributing to better inform management decisions. Vessel Monitoring System (VMS) and e-logbook data for the period 2012–2014 were used. The combined analysis of these data allowed the identification of fishing events and the estimation of the fishing intensity by gear type, as well as the characterization of general patterns relating to fishing operations. A total of 47 vessels displayed fishing activity in the studied area, mainly longliners based either on the mainland or the Madeira archipelago, visiting different seamounts in fishing trips lasting two to three weeks, and a few pole and line bait boats. Bottom and pelagic longlining alternate throughout the year, the former mostly in spring and summer, targeting the wreckfish Polyprion americanus and the European conger, Conger conger, while the latter is carried out in autumn and winter using a surface longline targeting the swordfish Xiphias gladius and a drifting longline set deeper in the water column, targeting the black scabbard fish Aphanopus carbo . A global evaluation of the fishing intensity and estimation of fishing impact in this area calls for the availability of VMS data, e-logbooks and landing declarations from non-Portuguese fleets, making monitoring in these areas a top priority to assess the sustainability of human activities. Highlights: The fishing activity of Portuguese vessels operating in Madeira-Tore (NE Atlantic) was analyzed using VMS and e-logbook data Several fisheries were identified in the area, differing in intensity and in spatial patterns of vessels activity For a global evaluation of fishing activity, data on the activity of non-Portuguese fleets need to be made available